Orthodontic Treatment of Ankylosed Maxillary Incisor through Osteogenic Distraction and Simplified Biomechanics - Daniel Gheur Tocolini; Priscila de Oliveira Silva; Iduilton Grabowski; Julia Carelli; Nathaly Dias Morais; Gisele Maria Correr; Francielle Topolski; Alexandre Moro (Case Reports in Dentistry)
Ankylosed teeth may have a significant esthetic and functional impact especially at the anterior segment of the upper arch. Treatment of ankylosed teeth is challenging. The objective of this case report is to describe a clinical case in which an ankylosed tooth was treated with the use of osteogenic distraction associated with simplified orthodontic biomechanics. A 17-year-old female Caucasian patient presented with a Class II malocclusion, severe maxillary dental crowding, moderate mandibular dental crowding, anterior open bite, upper midline deviation to the right, and upper right central incisor in infraocclusion due to ankylosis. Treatment involved the use of the ankylosed tooth as anchorage for the distalization of the right upper segment to correct the Class II malocclusion and to create space prior to surgery. After one week of surgical osteotomy, traction of the tooth and bone segment was initiated with the use of intermaxillary elastics. The ankylosed tooth was moved to the desired position. Bone formation and mucogingival tissue adaptation were observed. Thus, esthetic and functional improvement was achieved. Osteogenic distraction associated with simplified orthodontic biomechanics is an alternative to the treatment of ankylosed teeth which can replace the use of distractor screws, making treatment simpler and more accessible.